2019
DOI: 10.1080/0142159x.2019.1665634
|View full text |Cite
|
Sign up to set email alerts
|

Instructional design quality in medical Massive Open Online Courses for integration into campus education

Abstract: Purpose: Medical Massive Open Online Courses (MOOCs) are of interest for campus education. With growing interest in integrating medical MOOCs, their quality must be ensured. This however, has not been studied. We investigated if medical MOOCs meet the instructional design principles: problem-centeredness, activation, demonstration, application, integration, collective knowledge, collaboration, differentiation, authentic resources, feedback, and goal-setting. Methods: An overview of medical MOOCs and inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
1
26
0
3
Order By: Relevance
“…MOOCs intend to expose students to new disciplines, stimulate new interests, learn ideas, and create a learning community [4]. In medical education, several MOOCs are now delivered as independent education or as a complement to classroom courses [5]. During COVID-19, MOOCs become an opportunity for distance learning about topics of interest to users.…”
Section: Introductionmentioning
confidence: 99%
“…MOOCs intend to expose students to new disciplines, stimulate new interests, learn ideas, and create a learning community [4]. In medical education, several MOOCs are now delivered as independent education or as a complement to classroom courses [5]. During COVID-19, MOOCs become an opportunity for distance learning about topics of interest to users.…”
Section: Introductionmentioning
confidence: 99%
“…However, incorporating Merrill's first principles of instruction is sometimes neglected in designing MOOCs (Margaryan et al, 2015). Likewise, Hendriks et al (2020) showed that the activation and demonstration principles are less emphasised, and the integration is the most neglected principle in designing MOOCs. Also, Badali et al (2018) reported that Merrill's first principles of instruction are poorly incorporated in designing the MOOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing number of medical and healthcare MOOCs available, it is important that they are evaluated properly to determine their success in achieving their short-term and long-term learning aims and objectives. This in turn will help to ensure that their quality or performance is upheld, and areas for improvement are identified for future learners 20 21. There is also a lack of qualitative work exploring why learners decided to do the course, whether it met their expectations and how it influenced their everyday practice.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the quality of MOOCs has focused on the instructional design quality of MOOCs, and proposed various principles considered to be important for quality assurance check purposes 20 22 23. A recent study assessing the instructional design of medical MOOCs found that application, authentic resources, problem-centeredness and goal-setting existed in many courses, however, activation, collective knowledge, differentiation and demonstration were present in less than half of the courses, and integration, collaboration and expert feedback were only found in <15% of the MOOCs 20. According to Hood and Littlejohn (2016), a MOOC’s quality depends on the MOOC’s goals and the learner’s perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation